Genetic diversity of sago palm (Metroxylon sagu) accessions based on plastid cpDNA matK gene as DNA barcoding - Barahima Abbas; IHWAN TJOLLI; MUNARTI (Society for Indonesian Biodiversity, 2020)
Abstract. Abbas B, Tjolli I, Munarti. 2020. Genetic diversity of sago palm (Metroxylon sagu) accessions based on plastid cpDNA matK gene as DNA barcoding. Biodiversitas 21: 219-225. Metroxylon sagu Rottb is one of the plant species including in the Palmae family that deposits starch in the trunk. Sago palm was reported has high capability to produce a large amount of starch and large variation starch qualities which were mostly influenced by genetic factors. The objectives of this study are revealed sequence chloroplast DNA (cpDNA) associated with matK genes for the genetic diversity identification of sago palm accessions. Plant materials used in the studies were derived from Sago Research Center (SRC) collection. DNA extraction has adopted the procedure of Plant Genomic DNA Mini Kit. Polymerase chain reaction (PCR) was performed by using primer sets of MatK-1RKIM-f and MatK-3FKIM-r. DNA PCR product was sequenced by the 1st Base Asia, Singapore. Results of the study showed that the cpDNA sequence associated with matK genes in the genome of sago palm showed differences among accessions. Molecular diversities of sago palm accessions based on matK gene showed sago palm accessions separated into two genotypes. Genotype-1 incorporated of ten individuals of 15 accessions and genotype-2 incorporated five individuals of 15 accessions. A mutation site and deletion site occurred in the sequences of matK gene of the Genotype-2. Ten of the 15 sequences of the matK gene (belong to Genotype-1) were registered in the GenBank, NCBI as DNA barcoding and authenticity of sago palm germplasm from Papua islands, Indonesia territorials.